DEVELOPING PICTURE AS A MEDIUM OF TEACHING WRITING DESCRIPTIVE TEXT AT SMP NEGERI 5 TANJUNGBALAI - Rizki Ramadhansyah. P; Masitowarni Siregar (Universitas Negeri Medan, 2017)
This research is aimed at developing good picture as a media, interest and easy to be learnt, and can be used for teaching writing descriptive text. This study is developmental research uses Borg and Gall model. The subject of this research is the class VIII 4 of SMP Negeri 5 Tanjungbalai which consists of 35 students. The evaluators of the media are two experts. This instruments employed in this study are observation, questionnaires and test. The finding of the study is the quality of the developed picture media viewed from the experts is excellent (87,5%). The final product of this picture media is continued with effectiveness exam. The samples are 35 students which is given a sequence pictures of pet. Test were administrated to measure students’ ability in writing descriptive text by using picture and also for testing the product. The scoring system was based on five aspects; they are content, organization, vocabulary, language use, mechanics. The result shows that there is an increase of students’ ability in writing descriptive text by using picture as a medium. Therefore, the writer suggest to English teacher to develop picture as one of the alternative ways to increase the students’ descriptive text writing ability.